Dispersion Performance of Polycarboxylate Terpolymers with Different Alkyl Side-Chain Lengths in Pesticide Suspension Concentrate - Xiaodong Yang; Tianrui Ren; Bo Zhang (International Journal of Chemical Engineering)
A versatile dispersant plays a critical role in the suspension stability of pesticide suspension concentrate (SC) systems. Herein, a series of novel acrylate ester-based polycarboxylate terpolymers (PTs) were designed as dispersant for pesticide suspension concentrate and successfully synthesized in aqueous solutions from the copolymerization of α-methacrylic acid, allyl polyoxyethylene ether, and acrylate (methyl acrylate, ethyl acrylate, and n-butyl acrylate). Terpolymers were characterized by FT-IR and 1H-NMR to confirm their structure. The surface activities of PTs were evaluated according to critical micelle concentration (CMC) and the surface tension at CMC (γCMC). PT-3 with the longest alkyl side-chain length displayed the most superior surface activity due to its lowest CMC value compared with that of the other PTs. Additionally, the dispersion properties of PTs as dispersants in a 600 g/L imidacloprid SC were evaluated. Results showed that compared to the other two PTs, PT-3 contributes to the excellent dispersion properties on imidacloprid SC. Meanwhile, the obtained SC system exhibited shear thinning behavior under high-speed shearing showing typical features of pseudo-plastic non-Newtonian fluids, which conforms to the Herschel–Buckley model. Our results revealed that the effect of the alkyl side-chain length of dispersants could be considered the primary modulator of dispersion performance of SCs.